PENGARUH KOMPETENSI DOSEN DAN PROSES PEMBELAJARAN TERHADAP KEUNGGULAN BERSAING PROGRAM STUDI DI PENDIDIKAN TINGGI - Sahyar Sahyar (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
The research aims to study and analyze the influence of lecturer’s competence and learning process on study program competitive advantage either in simultaneous and partiality at private higher education in North Sumatera. This research was conducted by census methods over 44 S1 Management studies in Private Higher Education Kopertis of Regional I North Sumatera. The data used in this research were primary data collected by questioners. The research respondents were head and students of study programs. The validity and reliability of the data was tested before hypothesis testing. The data analysis for hypothesis testing was the path analysis. This research concludes that: the role of lecturer’s competence and learning process influential significantly toward study program competitive advantage. Partially from both independent variables, the influence of lecturer’s competence toward study program competitive advantage is greater than learning process.